(untitled) (Journal of Kidney Cancer, 2025)
Clear cell renal cell carcinoma (ccRCC) is marked by aberrant hypoxia-driven signaling and enhanced angiogenesis mediated by hypoxia-inducible factor 1-alpha (HIF-1α) and vascular endothelial growth factor alpha (VEGF-α). Zinc (Zn), an essential trace element with emerging anticancer potential, was evaluated for its ability to modulate angiogenesis in von Hippel–Lindau (VHL)-deficient 786-0 cells under normoxic and hypoxic conditions. Using quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting, enzyme-linked immunosorbent assay (ELISA), and immunofluorescence, we observed that Zn treatment reduced HIF-1α expression and VEGF-α secretion across both oxygenation states. Notably, Zn inhibited the hypoxia-induced nuclear accumulation of HIF-1α and attenuated paracrine endothelial activation, as shown by reduced human umbilical vein endothelial cell (HUVEC) viability in conditioned media assays. These effects likely involve transcrip-tional repression, enhanced proteasomal degradation of HIF-1α, and interference with VEGF-α–dependent signaling. Overall, our findings suggest that zinc may function as a multifunctional modulator of tumor angiogenesis and holds potential as an adjuvant in antiangiogenic strategies, particularly under hypoxic conditions.